PEMBINAAN BIMBINGAN MEMBACA QUR’AN (BMQ) DALAM MENINGKATKAN KUALITAS BACAAN SISWA DI SMA NEGERI 3 PALANGKA RAYA - Savira Dwi Kurnia; Abdul Aziz; Muhammad Azmi (Publikasi Inspirasi Indonesia, 2024)
This study aims to evaluate the effectiveness of the Qur'an Reading Guidance (BMQ) program in improving the quality of student reading at SMA Negeri 3 Palangka Raya. The method used is service learning, where students act as mentors to provide Qur'an reading guidance to 40 students for several sessions. Data collection was done through reading quality tests, observations, and interviews. Results showed significant improvement, with students' average reading score increasing from 65 in the pre-test to 85 in the post-test. Students also reported increased confidence and understanding of correct reading techniques. The program proved that an interactive and participatory approach to learning can have a positive impact not only on Qur'an reading skills, but also on students' character development. The findings recommend implementing similar models in other schools to strengthen religious education in Indonesia.